Cultural differences in politeness as a function of status relations: Comparing South Korean and British communicators. (28th November 2018) - Moon, Chanki; Uskul, Ayse K.; Weick, Mario
Abstract: Although politeness is an important concern in communications across cultures, a prevalent assumption in psychology is that East Asians are more inclined to be polite than members of other cultural groups due to prevalent cultural norms. Yet, evidence for this assumption is mixed. The present research examined this issue by considering the role of social hierarchy in interpersonal communications of Korean and British participants ( N  = 220) using an experimental task that involved writing an email to decline a request made by a junior or a senior person. The results showed that Korean participants' emails were more polite when addressing a senior colleague compared with a junior colleague in work contexts. In contrast, recipient status did not impact British participants' politeness. Crucially, cultural differences in politeness only emerged when participants addressed a senior colleague, but not when participants addressed a junior colleague. We discuss the implications of these findings and directions for future research.